A Ethnobotanical survey of medicinal plants consumed during holy month of Ramadan in Chlef region, Algeria - Merouane, Abdelaziz; Fellag, Sara; Touaibia, Moufida; Beldi, Abdelmalek (Ethnobotany Research and Applications, 2022)
Background: The fasting month of Ramadan is the fourth pillar of Islam. This religious practice is characterized by a specific style of life, culinary and phytotherapeutic habits in Muslim societies. The aim of this research is to document information about the traditional medicinal knowledge of herbal species used during the holy month of Ramadan in the region of Chlef, north-west Algeria. Methods: This ethnobotanical survey was conducted during the holy month of Ramadan in 1442 Hijrah, corresponding to 13 April–12 Mai 2021. The information was gathered through semi-structured interviews with 100 fasting Muslim informants ranging in age from 18 to 71 years. The obtained data were analyzed using the following indices: Use Value (UV), Family Use Value (FUV) and Informant Consensus Factor (ICF). Results: In the current and first Ramadanian ethnobotanical survey, 38 herbal species distributed into 22 families were recorded in the Chlef region, north-west Algeria. Lamiaceae was the dominant botanical family explored in phyto-folk medicine, with 8 species. Leaves and aerial parts (22.22% each) represent the main plant parts valorized. Decoction (32.35%) and infusion (27.94%) were the principal preparation methods adopted for making remedies from medicinal herbs. Species supported by Quran verses and prophetic orientation are widely consumed during the month of Ramadan and record UVs indexes superior to 0.5. The highest UV values were assigned to Phoenix dactylifera L. (0.98), Hordeum vulgare L. (0.92) and Citrus limon (L.) Osbeck (0.89). The analyses revealed a high and common ICF among the local population during the month of Ramadan for 14 disease categories due to the religious guidance of informants. Conclusions: The month of Ramadan is characterized by a rich patrimony of herbal medicine and harmonious knowledge among informants based essentially on religious orientation. Further investigations into possible interactions between the health benefits of fasting and the therapeutic virtues of medicinal herbs are suggested in the future. Keywords: Ethnomedicine, Iftar, Suhur, Ramadan, Prophetic medicine.